2011
DOI: 10.1590/s0103-51502011000100014
|View full text |Cite
|
Sign up to set email alerts
|

Tempo de início da atividade elétrica dos estabilizadores patelares na marcha em sujeitos com e sem síndrome de dor femoropatelar

Abstract: INTRODUÇÃO: A síndrome de dor femoropatelar (SDFP) é um problema comum que afeta uma em cada quatro pessoas. A alteração no tempo de ativação e a intensidade de contração dos músculos vasto medial oblíquo (VMO) e vasto lateral (VL) são consideradas fatores importantes na etiologia da SDFP. No entanto, existem poucos estudos sobre a função da porção oblíqua do vasto lateral (VLO) e nenhum sobre o tempo de ativação (onset) do VLO em atividades funcionais em sujeitos normais e com SDFP. OBJETIVO: Assim, o objetiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
(21 reference statements)
0
4
0
2
Order By: Relevance
“…Augusto et al 14 verified that the intensity of muscle activation increases with the use of neuromuscular electrical stimulation (NMES), which makes it suitable in cases of PFD, since the greater incidence of this dysfunction is related to muscular imbalance, which corroborates the study by Bevilaqua-Grossi et al, 15 where a difference is observed in the reflex activation time between the Vastus Medialis Obliquus (VMO) and Vastus Lateralis Obliquus (VLO) muscles, both in healthy individuals and in patients with PFD. Santos et al 16 . compare the vastus medialis obliquus (VMO), vastus lateralis longus (VLL) and vastus lateralis obliquus muscle activation time during a walk on the treadmill with 27 individuals, 15 of whom were healthy and 12 had PFD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Augusto et al 14 verified that the intensity of muscle activation increases with the use of neuromuscular electrical stimulation (NMES), which makes it suitable in cases of PFD, since the greater incidence of this dysfunction is related to muscular imbalance, which corroborates the study by Bevilaqua-Grossi et al, 15 where a difference is observed in the reflex activation time between the Vastus Medialis Obliquus (VMO) and Vastus Lateralis Obliquus (VLO) muscles, both in healthy individuals and in patients with PFD. Santos et al 16 . compare the vastus medialis obliquus (VMO), vastus lateralis longus (VLL) and vastus lateralis obliquus muscle activation time during a walk on the treadmill with 27 individuals, 15 of whom were healthy and 12 had PFD.…”
Section: Discussionmentioning
confidence: 99%
“…Santos et al . 16 compare the vastus medialis obliquus (VMO), vastus lateralis longus (VLL) and vastus lateralis obliquus muscle activation time during a walk on the treadmill with 27 individuals, 15 of whom were healthy and 12 had PFD. At the end of the study they observed a difference between VMO and VLL, where in the individuals with PFD the activation order started with VLL followed by VLO and finally VMO, while in the individuals without PFD the order was inverted, starting with VMO, followed by VLO and lastly VLL.…”
Section: Discussionmentioning
confidence: 99%
“…approximately 11 cm above the superolateral edge of the patella with an inclination of 15° to the femur axis 20 . For the placing of the VLO electrodes the lateral epicondyle of the femur and the beginning and middle of the muscle belly were located with an inclination of 50° in relation the femur axis 20 . The reference electrode was attached right above the lateral malleolus.…”
Section: Methodsmentioning
confidence: 99%
“…No GC, foram analisados os dados do membro dominante, o qual foi determinado pelo membro que os sujeitos utilizavam para chutar uma bola. 19…”
Section: Cinemáticaunclassified
“…In the CG, the dominant limb data were analyzed, which was determined by the limb that the subjects used to kick a ball. 19 …”
Section: Data Processingmentioning
confidence: 99%